Analisis Determinan Kejadian Stres Kerja pada Pegawai Rumah Sakit Nasional Diponegoro Semarang Selama Pandemi Covid-19 - Rosalia, Marcheda Rahma; Jati, Sutopo Patria; Budiyanti, Rani Tyas (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Hospital is one form of health facilities, organized by the community to carry out basic health efforts or health referrals and supporting health efforts. Nurses and employees as one of the professions in the hospital have an important role in the implementation of health services. The main task of a hospital employee is to serve and care for patients to speed up the healing process. Because of its dynamic work, a nurse and employee need to have good body condition, healthy, and have enough energy. Unfavorable body conditions result in a nurse easily discouraged when while working he experienced physical fatigue, emotional exhaustion, and mental fatigue.. Work stress is an emotional and physical response that is disturbing or detrimental that occurs when the demands of the task are not in accordance with the ability, resources, or desires of the worker. The purpose of this study was to look at factors related to work stress events such as workload, work shifts, social support, and out-of-work activities at employees of Diponegoro National Hospital Semarang during the Covid-19 Pandemic. This research uses this type of analytical survey research with cross sectional methods. The population in this study was 83 employees. The total sample size is 83 employees. Data analysis using Chi square correlation test with significance level of 0.05. The results showed that the characteristics of respondents in this study were the majority of respondents with female gender (67.5%), young adulthood (24 - 29 years), Poly Outpatient work (12%), and working life 0-4 years (48.2%). There is a relationship between work stress and workload and work stress with work, while variable social support, and activities outside of work have no significant relationship with work stress in employees of Diponegoro National Hospital Semarang during the Covid-19 pandemic.